Exchange Rate as a Determinant of Foreign Direct Investment: Does it Really Matter? Theoretical Aspects, Literature Review and Applied Proposal (2020)
This paper re-examines the role of exchange rates as determinant of FDI. It extends the analysis to include the issue of how exchange rates determine the decision of invest in one country depending on whether the firm is deciding to invest on the country to service the local market or to invest on the country in order to re-export. This paper offers a broad literature review of the state of the empirical research in order to draw conclusions of the real importance of the exchange rate as a determinant of FDI. Details of FDI current behavior in Latin American are described and I propose a model of FDI to be applied for these countries. Data sources are given.